Implementing Local Wisdom Through Project-Based Learning in ELT and Pancasila Student Profile - Fani, Armin; Novi Nurdian; Novi Suma Setyawati (Universitas Muhammadiyah Kalimantan Timur, 2025)
This study delves into implementation of local wisdom through project-based learning (PjBL) in English language teaching (ELT) and Pancasila student profiles development program. Conducting through interview research principles, this study aims at describing the implementation phases of local wisdom through PjBL in ELT and Pancasila student profiles development program and its constraints. The participants of this study are school principals, three English teacher, and two students. In-dept interviews were conducted as data collection technique. The finding of this shows that the implementation covers planning, integrating, and assessing phases. The finding also elaborates some practical constraints. While providing valuable information, this study acknowledges its limitation and offers suggestion for future research.